Prion-like domain mediated phase separation of ARID1A promotes oncogenic potential of Ewing’s sarcoma - Kim, Yong Ryoul; Joo, Jaegeon; Lee, Hee Jung; Kim, Chaelim; Park, Ju-Chan; Yu, Young Suk; Kim, Chang Rok; Lee, Do Hui; Cha, Joowon; Kwon, Hyemin; Hanssen, Kimberley M.; Grünewald, Thomas G. P.; et al. (Nature Communications, 2024)
Liquid-liquid phase separation (LLPS) facilitates the formation of membraneless organelles within cells, with implications in various biological processes and disease states. AT-rich interactive domain-containing protein 1A (ARID1A) is a chromatin remodeling factor frequently associated with cancer mutations, yet its functional mechanism remains largely unknown. Here, we find that ARID1A harbors a prion-like domain (PrLD), which facilitates the formation of liquid condensates through PrLD-mediated LLPS. The nuclear condensates formed by ARID1A LLPS are significantly elevated in Ewing’s sarcoma patient specimen. Disruption of ARID1A LLPS results in diminished proliferative and invasive abilities in Ewing’s sarcoma cells. Through genome-wide chromatin structure and transcription profiling, we identify that the ARID1A condensate localizes to EWS/FLI1 target enhancers and induces long-range chromatin architectural changes by forming functional chromatin remodeling hubs at oncogenic target genes. Collectively, our findings demonstrate that ARID1A promotes oncogenic potential through PrLD-mediated LLPS, offering a potential therapeutic approach for treating Ewing’s sarcoma.